Analisis Ecological Footprint Sistem Perikanan di Kawasan Taman Wisata Perairan Gili Matra, Lombok Utara - Made Ayu Pratiwi; Yusli Wardiatno; Luky Adrianto (Jurnal Ilmu Pertanian Indonesia, 2014)
Gili Matra Aquatic Park is a conservation area located in Gili Indah Village, North Lombok. It is one of marineprotected areas that has a wide range of potential resources, i.e. fish resources and ecosystems. The potency offish resources and marine ecosystems is utilized in fisheries and tourism activities. Non responsible fisheries andtourism activities can cause ecosystem degradation and fish extinction. The existence and preservation of fishresources is the main key to successful fisheries management in Gili Matra. Therefore, it is necessary to study theecological footprint to estimate the carrying capacity of fisheries in Gili Matra Aquatic Park. This study wasconducted in May June at TWP Gili Matra. The ecological footprint analysis showed that EF in Gili Indah village is0.1 x 10-6 km2/kapita. When the population of Gili Indah village in 2014 are 3.694 people, the area of EF is 0.55 km2.Compared with 18.97 km2 sustainability fisheries zone of TWP Gili Matra, so this is referred to undershoot. The useof EF fishery is still smaller than available area and the resources can reproduce and maintain its ecologicalfunctions.